The value chain of heat production from woody biomass under market competition and different intervention systems: An agent-based real options model - Matthias Wolbert-Haverkamp; Jan-Henning Feil; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2014)
Woody biomass in terms of short rotation coppice (SRC) could be a promising alternative for producing biomass to generate renewable energy. Even through, from a single farms point of view, SRC seems to be an interesting land use alternative, farmers do not cultivate SRC. Some studies found out that the real options approach (ROA) could at least partially explain farmers' inertia of cultivating SRC. Nevertheless, those studies do not take into account market competition between farmers and farmers' fear of not having an outlet market in order to dispose the harvested wood chips. This inertia can also cause an investment reluctance concerning building biomass heating stations. In the present study therefore, we focuses on the whole value chain from producing wood chips over generating energy and selling the energy to the end-consumers. We develop an agent-based model which is able to consider market competition and can picture the whole value chain. In order to further motivate farmers to cultivate SRC different types of incentives offered by the biomass heating station are investigated. Our results show that if no incentive system is offered, farmers cultivate SRC reluctantly which leads to a loss of profit of the biomass heating station. With regard to an investment subsidy, it needs to be equal to approximately 300% of the capital costs of investment to strongly motivate farmers to produce enough wood chips that largely decrease the loss of profit of the biomass heating station. If a price floor is offered, farmers' additional amount of wood chips produced is very small. Therefore, the loss of profit does not significantly decrease if the price floor amounts to 95%.
Keywords: 330; real options; value chain; competition; incentive systems; biomass; short rotation coppice